Pojavnost arhitekturne membrane iz lesenih lamel - Marolt, Peter (Les (Ljubljana), 2002)
In the paper, beside the applicative aspect of wood used in the construction of an elevation hull, its time and spiritual components have been stressed in the first place. In contemporary architecture, isolation and privacy are confronted with environmental influences. The article examines the phenomenon of a double membrane - the interior central shell and the exterior semi-transparent membrane made of wood lamellas. The later represents a barrier that separates the public sphere from the private premises, it delineates the private space and serves as an insulating mantle. It intercepts meteorological impacts and other people's glimpses into the interior of a building. I point out to the probable origin of the concept of a double membrane in the vernacular architecture and to the significance of wood as a humane material. Onetime heavy timber walls remain only a memory and the thickness of wood used for the construction of elevation mantle diminishes novodays. Wood as a material for the construction of the exterior membrane can conceal a cold reinforced wall. It remains a roommate of a dwelling and its spiritual dimension. The respect of the importance of legacy could improve the quality of the contemporary design.
Keywords: lesene obloge; stanovanjska arhitektura; hiše